Middle and High School Students with Visual Impairments Describe Their Experiences in Learning a New Braille Code for Mathematics and Science - Tina S. Herzberg; C. Rett McBride
Introduction: When the United States adopted Nemeth Code within Unified English Braille (UEB) Contexts and UEB Math/Science in 2016, students who were using braille had to learn a new code for science, technology, engineering, and mathematics (STEM). In late 2016, Bell and Silverman surveyed students about their initial experiences transitioning to a new braille code. However, to date there has not been additional research that includes students$1 (Bperspectives regarding the long-term effect of the transition to a new braille code on their ability to learn. The purpose of this study was to learn about students$1 (Bexperiences in transitioning to a new braille code, whether students receive STEM braille materials in a timely manner, the technology students use in STEM, and what advice students have for teachers of students with visual impairments. Methods: In the spring of 2021, 11 middle and high school students who use braille for STEM classes participated in one of three focus groups. The data were analyzed using open-coding methods. Results: All participants had initially learned the Nemeth Braille Code for Mathematics and Science Notation and subsequently transitioned to one of the new braille codes. Students typically characterized learning a new braille code as easy. Most of the students had experienced delays in receiving braille materials, which sometimes negatively affected their ability to learn. Students reported using a variety of mainstream and assistive technologies. Discussion: Students should have consistent access to high-quality STEM materials in a timely manner in the braille code that they prefer. The students in this study articulated their preferences and were willing to advocate for themselves to overcome learning challenges in their STEM courses. Implications for Practitioners: Teachers of students with visual impairments can partner with general education STEM teachers and administrators to resolve persistent issues. Teachers can encourage students to voice their preferences and assist students in developing strategies before challenges arise.s